Structure of human lysosomal acid α-glucosidase–a guide for the treatment of Pompe disease. Issue 1 (December 2017) - Roig-Zamboni, Véronique; Cobucci-Ponzano, Beatrice; Iacono, Roberta; Ferrara, Maria Carmina; Germany, Stanley; Bourne, Yves; Parenti, Giancarlo; Moracci, Marco; Sulzenbacher, Gerlind
Abstract Pompe disease, a rare lysosomal storage disease caused by deficiency of the lysosomal acid α-glucosidase (GAA), is characterized by glycogen accumulation, triggering severe secondary cellular damage and resulting in progressive motor handicap and premature death. Numerous disease-causing mutations in thegaa gene have been reported, but the structural effects of the pathological variants were unknown. Here we present the high-resolution crystal structures of recombinant human GAA (rhGAA), the standard care of Pompe disease. These structures portray the unbound form of rhGAA and complexes thereof with active site-directed inhibitors, providing insight into substrate recognition and the molecular framework for the rationalization of the deleterious effects of disease-causing mutations. Furthermore, we report the structure of rhGAA in complex with the allosteric pharmacological chaperone N-acetylcysteine, which reveals the stabilizing function of this chaperone at the structural level. Pompe disease is caused by mutations in lysosomal acid α-glucosidase (GAA) and patients are being treated with recombinant human α-glucosidase (rhGAA). Here the authors present the crystal structures of rhGAA and its complexes with inhibitors and a pharmacological chaperone, which is important for drug development.